Chemical Control of Wild Sorghum [Sorghum arundinaceum(Del.) Stapf.] in Faba Bean (Vicia faba L.) in the Northern State of Sudan - Bedry, Kamal A. M.; Elamin, Abbas E. M. (University of Khartoum Journal of Agricultural Sciences, 2023)
An experiment was conducted at Merowe Research Station farm, in the Northern State, Sudan, during 2008/2009 and 2009/2010 seasons. The objectives of the experiment were to determine the damage inflicted by a wild sorghum species (Sorghum arundinaceum (Del.) Stapf.) on the yield of faba bean (Vicia faba L.) and to evaluate the efficacy of the post-emergence herbicide clodinafop-propargyl (Topik) on wild sorghum and its effect on faba bean yield. The wild sorghum reduced faba bean crop stand and straw and seed yields by 53% -76%, 76% -79% and 88% - 91%, respectively, compared with the hand-weeded control. Faba bean was tolerant to the herbicide. The herbicide, at all rates, effected complete (100%) and persistent control of the wild sorghum and resulted in faba bean seed yield comparable to the hand- weeded control. The lowest dose (0.075 kg a.i./ha) of the herbicide used was equal to 75% of the dose recommended for the control of wild sorghum in wheat. It is concluded that clodinafop-propargyl at 0.075 kg a.i./ha could be used in controlling wild sorghum in faba bean. At this rate, the marginal rate of return was about 35 which indicating that every monetary unit (SDG 1) invested in the mentioned treatment would be returned back, plus additional amount of 35 SDG.